THE URGENCY OF IMPLEMENTING THE STANDARD OF PROOF IN CRIMINAL CASE TRIALS FOR THE DISCLOSURE OF MURDER OFFENSES - Restika Ndruru; Muhammad Arif Sahlepi; Muhammad Azhali Siregar (RADJA PUBLIKA, 2026)
The crime of murder is classified as a serious offense because it involves the loss of life, which constitutes the most fundamental human right. The judicial process for the perpetrator must be conducted meticulously, transparently, and fairly. One of the key elements in criminal law enforcement to uncover the truth in murder cases is the standard of proof, namely the judge’s conviction based on at least two valid pieces of evidence as stipulated in Article 183 of the Indonesian Criminal Procedure Code (KUHAP). This study employs a normative juridical approach, which views law as a binding written norm that serves as the basis for resolving legal issues. Data were collected through library research by examining and analyzing various relevant sources such as books, journals, articles, and other scholarly works, both printed and online. The data were analyzed qualitatively, focusing on the examination of legal materials derived from legislation, literature, and related documents.